A person‐centred approach to family carer needs assessment and support in dementia community care in Western Australia. (10th April 2018) - Aoun, Samar M; Toye, Chris; Slatyer, Susan; Robinson, Andrew; Beattie, Elizabeth
Abstract: This feasibility study aimed to identify and address the support needs of family carers (FCs) of people living with dementia and to assess whether the use of the Carer Support Needs Assessment Tool (CSNAT) intervention in home‐based care was acceptable and relevant to FCs. The CSNAT intervention comprised two FC support needs assessment visits, 7 weeks apart, plus associated actions addressing prioritised needs by the Client Care Advisors of a community care service in Western Australia in 2015. Telephone interviews were conducted with FCs on their experience using the CSNAT at the end of the intervention. Twenty‐one FCs were involved in the intervention and 15 of them completed the feedback interviews. Care recipients had moderate to severe dementia. The top five support needs reported by FCs were: having time to yourself in the day; knowing what to expect in the future; practical help in the home; looking after your own health and dealing with your feelings and worries. Three themes summarised their experience: a straightforward structured approach; awareness, acknowledgement and acceptance of their situation; and provision of support. FCs appreciated the opportunity to be heard and acknowledged, to have their practical and psychosocial support needs facilitated, to identify what is important to them and to receive a response in a timely manner. The CSNAT approach offered a structured carer‐led, person‐centred, supportive intervention that facilitated discussion between the family carer and the service provider about support needs and strategies to address them.